Quiet gardens the roots of faith? - Bowden-Pickstock, Susan (London ; New York : Continuum, 2009)
Quiet Gardens is an exploration of horticulture as a medium for meaning and for spirituality. In an increasingly secular age when absolute values are taboo, political correctness reigns supreme, and our lives orbit Planet Consumer, we need experiences to balance the emphasis on material acquisitions. Internationally, tensions are running high in the global village and environmental issues are at the top of the agenda. The shadow of terrorism emphasises ideological differences, but it also draws together those living underneath it: inter-faith and ecological conversations have become necessitie
PART ONE: FOOD FOR THOUGHT; 1. Journey's beginning; 2. Journey into meaning; 3. Relational gardens; 4. Journey into identity; 5. Gardens as therapy; 6. Iconic gardens; PART TWO: THE QUIET GARDEN MOVEMENT; 7. Behind the garden gate; 8. Arley, Worcestershire; 9. Rydal, Cumbria; 10. Epworth, Lincolnshire; 11. Bridlington, The East Riding of Yorkshire; 12. Petworth, West Sussex; 13. Clehonger, Herefordshire; 14. Exmouth, Devon; 15. White Waltham, Berkshire; 16. Charlcombe, Bath and North Somerset; 17. Musgrave, Westmoreland; 18. Canterbury, Kent; 19. Stainforth, South Yorkshire
Includes bibliographical references (p. 173-174).
Description based on print version record.
Keywords: Spiritual life; Gardens -- Religious aspects; Gardens -- England; Spirituality; Religion; RELIGION -- Inspirational; SELF-HELP -- Spiritual; Electronic books